Characterisation of Cellulose Nanofibres Derived from Chemical and Mechanical Treatments - Martini, Muhamad; Hornsby, Peter; Carmichael, Eugene; Muhammad, Zakaria; Seok, Yew Been; Mohamed, Saiful; Sharma, Shekhar (2019)
Optimised routes have been established to obtain high aspect ratio cellulose microfibrils derived from plant feedstocks, involving a combination of a chemical and mechanical treatment using a high pressure microfluidizer. By this means, nano-cellulose was produced using different pretreatment protocols. The nanofibres produced were characterised for its particle size distribution measurement (laser diffraction and zeta potential analysis) and fourier transform infrared for its structural analysis. Results obtained and subsequent trends observed in chemical, mechanical and chemo-mechanical treated nanofibres were compared and contrasted. The chemomechanical treatment (TEMPO-oxidation and high pressure microfluidisation) yielded higher aspect ratio nanofibrils than nanofibrils made by solely chemical or mechanical treatment.